1987
DOI: 10.1038/bjc.1987.10
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone-induced DNA synthesis in cultured rat ventral prostate: effects of estracyt and its derivatives

Abstract: Summary Testosterone-induced DNA synthesis in cultured rat ventral prostate was used to compare the direct effects of EstracytR and EmcytR with that of their metabolite, estramustine, and their carrier-hormone, oestradiol-17/ on prostatic growth. In serum-supplemented medium (5-20% FCS), all the compounds were equally effective in suppressing testosterone stimulated DNA synthesis which was reduced by between 40-50%, whereas in serum-free medium the estramustine compounds were consistently less effective than o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The inhibition of androgen-induced BUG growth by Win 49,596 is comparable to previous reports of the effects of anti-androgens in organ culture. For example, Buchanan and Riches [21] showed that a 100-fold excess of cyproterone acetate decreased iododeoxyuridine uptake by 50% in cultured prostate. A 100-fold excess of cyproterone acetate or flutamide decreased prostatic acid phosphatase activity to one third of normal T-stimulated levels in vitro [22], while a 50-fold excess of cyproterone acetate decreased the growth of developing prostatic ducts in cultured urogenital sinus by 50% [12].…”
Section: Discussionmentioning
confidence: 99%
“…The inhibition of androgen-induced BUG growth by Win 49,596 is comparable to previous reports of the effects of anti-androgens in organ culture. For example, Buchanan and Riches [21] showed that a 100-fold excess of cyproterone acetate decreased iododeoxyuridine uptake by 50% in cultured prostate. A 100-fold excess of cyproterone acetate or flutamide decreased prostatic acid phosphatase activity to one third of normal T-stimulated levels in vitro [22], while a 50-fold excess of cyproterone acetate decreased the growth of developing prostatic ducts in cultured urogenital sinus by 50% [12].…”
Section: Discussionmentioning
confidence: 99%